Design and Performance Evaluation of a Digital Chlorinator for Domestic Wastewater Disinfection in Healthcare Facilities - Suyanto, Beny; Jayadi, Hurip (Gema Lingkungan Kesehatan, 2025)
Domestic wastewater from healthcare facilities such as hospitals, community health centres, and polyclinics contains organic loads, toxic chemical compounds, and pathogenic microorganisms that have the potential to cause environmental pollution and pose a risk to public health if not treated adequately. Various conventional treatment methods, including UV, ozonation, aeration, and biofiltration, have been used to reduce pollutants, but cost limitations, high energy requirements, and technical reliability make chlorination the preferred option because it is relatively inexpensive, easy to implement, and produces disinfectant residues that provide continued protection. However, uncontrolled use of chlorine can lead to excessive residues, disinfection by-products (DBPs), and operational inefficiencies. To address these challenges, this study aims to design and evaluate the performance of a digital chlorinator equipped with an automatic control system with dual energy source flexibility (AC/DC and solar panels). This study used a one group pre-test and post-test design with domestic wastewater samples from hospitals, health centres, and polyclinics in Magetan Regency. The water quality parameters analysed included pH, BOD, COD, ammonia, chlorine demand, residual chlorine, and total coliforms. Initial measurements showed BOD of 105–145 mg/L, COD of 198–260 mg/L, ammonia of 13–18 mg/L, and total coliform of 8.5 × 10⁵ to 1.2 × 10⁶ MPN/100 mL, far above the national quality standards. After treatment using a digital chlorinator with an optimum dose of 200 ppm, BOD decreased by 77–82%, COD by 72–78%, ammonia by 75–80%, and total coliforms by more than 99%, while the pH remained stable in the range of 7.1–7.3 and the chlorine residue was maintained at 0.2–0.5 mg/L according to the recommended standard. A comparison of energy sources showed that the effectiveness of solar cells was almost equivalent to that of AC/DC, with a small difference in the reduction of BOD and COD that was not statistically significant. The results of this study conclude that digital chlorinators are effective, adaptive, and have the potential to be an innovative solution in improving the quality of domestic waste treatment in health facilities, especially in areas with limited access to electricity, and can support the achievement of sustainable environmental health goals.